Learning Media in Pandemic: Autoplay Media Studio Added Stretching Motion to Evaluation Digestive System Subject - Primadya Anantyarta; Eka Mardiana (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2020)
Development of learning media with Autoplay Media Studio program accompanied by instructions for warm-up body in answering evaluations is based on the fact that during the Covid-19 pandemic this limited all student activity and learning. The decrease in the activity of student will disrupt the body's metabolism because just live at home or boarding house so that it is difficult to learn and even understand material when online lecturing. The addition of exercise warm-up instruction to this learning media aims to make students not only learn to understand material, but also practice their bodies during pandemic period they can still maintain body fitness. Development method uses five stages called the ADDIE model. Products in the form of media containing digestive system material with various types of data in the form of writing, images and videos combined in one compact disk. Two validators conducted an assessment of the correctness of the material content and media appearance. The results of media validation get a 98.61% and material validation get 98.53% score with very valid criteria and not revised. Results of product trials on 25 students showed 96% of students rated the appearance of the media as attractive and 4% rated the display in medium criteria. The use of media accompanied by warm-up movements, including the criteria for helping students learn independently in pandemic, was expressed by 68% of students, 24% of students stated that media was included in the medium criteria and 8% of students stated that the media could not help.